Plaints soient les Indiens du cosmos - Jane M. Young (Revue d'anthropologie des connaissances)
While since the late 1960s, Americans draw in the Native American culture hoping to give a sense of their life back in a materialist society, the NASA space programme reflects a cosmology and an ethos injuring Zuni cosmology. Far from the Western understanding of the outer space as composed of unliving bodies, Zuni cosmology lays on a holistic vision of the universe, where celestial bodies are personified regarding a rich and ancestral mythology. Thus, the Apollo space programme could be seen as its antithesis, but also as the translation of the historical opposition among Native and non-Native Americans. Because the analysis of a cosmology allows to highlight ideological mechanisms involved in the organization of a society and the latter’s policies, defining a space programme has to be thought in relation with the understanding of the universe and the role that human beings hold in it.